WHAT DO WE VALUE IN LITERATURE FOR CHILDREN? ONE DECADE THROUGH THE PRISM OF MAGNESIA LITERA - Schupplerová, Stanislava (Bohemica Olomucensia, 2020)
The article considers the awarded books Magnesia litera in the category of children's literature between 2009 and 2019. This mediated award largely contributes not only to shaping the image of Czech literature among the general public, but also affects book sales. We are therefore interested in what books, what genres and especially what qualities were awarded in the monitored decade.
Keywords: Czech literature; poetry; prose; literary prizes; children's literature